EFEKTIVITAS PENERAPAN KURIKULUM MERDEKA BELAJAR PADA KEMAMPUAN KOGNITIF MATEMATIKA SISWA MI TA’MIRUL ISLAM SURAKARTA - Dita Cahya Apriliya; Lailla Hidayatul Amin; Alfian Eko Rochmawan (Raudhah - Proud To Be Professional, 2023)
The implementation of the new curriculum, namely the independent learning curriculum, has an influence on students' cognitive abilities on the application of the curriculum, especially on the cognitive abilities of mathematics subjects. The purpose of this study was to determine the effectiveness of implementing the independent learning curriculum on the cognitive abilities of grade 4 students at MI Ta'mirul Surakarta. This research uses quantitative methods. The results of this study indicate that the implementation of the independent learning curriculum at MI Ta'mirul Islam Surakarta is in accordance with the learning system provided by the government. Cognitive abilities in the mathematics subject of grade 4 students before the implementation of the independent learning curriculum were in the moderate category with a percentage of 91.4%. Meanwhile, the cognitive abilities of grade 4 students after the implementation of the independent learning curriculum were also in the moderate category with a percentage of 81.4%. The effectiveness of the application of the independent learning curriculum on the cognitive abilities of grade 4 students in MI Ta'mirul Islam Surakarta is proven by the calculation of the hypothesis test with the comparative paired simple t test which has been carried out to obtain a value of 2.583